BIOCHEMICAL ASPECTS INFLUENCE REMEDIES AQUALIFT AND DMAE ON SOFT TISSUES AFTER MODELING RECESSION GUMS ON THE RATS - V. Zubachyk; M. Iskiv (Ukrainian Medical Stomatological Academy, 2016)
Aesthetic aspects remains the actual issue of dentistry, especially periodontology. It concerns not only the harmony in shape, size and color of teeth, but also the outline of lips and gums. Gum recession mainly is being treated by means of surgery. At the initial stages we have proposed to use the therapeutic approach using injection of synthetic drugs in order to recover lost soft tissue by lifting. The injection of drugs has been conducted after modelling the gum recession of rats in order to create a pathological condition similar to humans. When working with rats we have followed the international recommendations on biomedical research using animals. To eliminate the simulated aesthetic defect there have been used drugs to being injected based on synthetic compounds: hydrogel aqualift and 2- dimethylaminoethanol 4-aсetoaminobenzoat 6% (DMAE), into marginal edge of the gums in the area of the lower incisors of the oral cavity of rats. The animals got injections of appropriate medication into soft tissue of marginal gum twice with interval of 10 days. The experiment lasted for 30 days, after which the euthanasia of rats was performed by means of overdose of diethyl ether. Using the rat gingival tissue there have been prepared homogenates in the ratio of the mass of tissue to volume of saline 1:40. At + 4 ° C the homogenates were centrifuged at 2500g for 30 min. To identify the changes occurring in the connective tissue there were used biochemical research: there was measured the activity of alkaline (ALP) acid phosphatase, and catalase; protein-bound (PB) and free oxyproline (FO), glycosaminoglycans; in order to assess the intensity of lipid peroxidation in the gingival epithelial tissues in case of experimental recession in rats and following injections of medicines there have been assessed by accumulation of secondary products, such as the activity of malon dialdehyde (MDA). Condition of the antioxidant system was expressed by antioxidant-prooxidant index (API). The research showed high metabolic activity in the gingival tissue after introduction of internal mucosal plastic and contouring drugs.